Euchromatic domains in plant chromosomes as revealed by H4 histone acetylation and early DNA replication - Vyskot, B; Siroky, J; Hladilova, R; Belyaev, N D; Turner, B M (Genome, 1999)
Using specific polyclonal antisera raised against acetylated isoforms of histone H4, we have analyzed their distribution in the dioecious plant Silene latifolia (syn. Melandrium album) possessing heteromorphic sex chromosomes. Our previous studies on this species have shown that one of the two X chromosomes in homogametic female cells is heavily methylated and late replicating, as a possible consequence of dosage compensation. Here we report that there are no detectable differences in intensity and distribution of H4 acetylation between these two X chromosomes. In S. latifolia only distal-subtelomeric chromosome regions, on both the sex chromosomes and autosomes, display strong signals of H4 acetylation at N-terminal lysines 5, 8, and 12. These acetylated domains correspond to the very early replicating distal chromosome regions as revealed by 5-bromodeoxyuridine pulses followed by the indirect immunofluorescence microscopy. The distribution of H4 acetylated at lysine 16 was uniform along the chromosomes. The unique distal-subtelomeric H4 acetylation signals were also observed in three other Silene species (S. vulgaris, S. pendula, and S. chalcedonica), but not in two non-related plant species tested (Allium cepa and Nicotiana tobacum). The presented data as well as our recent studies on the structure of S. latifolia chromosome ends indicate that Silene species possess the specific distal-subtelomeric location of euchromatin, gene-rich regions on chromosomes.
Keywords: replikace DNA; kinetika; histony; acetylace; Histones; Kinetics; zvířata; DNA, Plant; králíci; Acetylation; DNA rostlinná; Rabbits; DNA Replication; Animals